TREE THINKING ABILITY AND PRE SERVICE BIOLOGY TEACHERS ACCEPTANCE OF EVOLUTION (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2017)
Tree thinking is a platform of thinking for interpreting phylogenetic tree. This study analyzed correlation between pre-service biology teachers’ tree thinking ability and their acceptance of evolution. Subjects were 41 pre-service biology teachers from two universities in West Java. Research instruments were TTCI (Tree Thinking Concept Inventory) and MATE (Measure of Acceptance of the Theory Evolution). Data was analyzed statistically. Result indicated that pre-service biology teachers’ tree thinking ability and their acceptance of evolution were categorized as moderate. Difference between gender as well as correlation between tree thinking ability and acceptance of evolution are discussed.
Keywords: Evolution; MATE; TTCI; acceptance of evolution; Tree thinking